2019
DOI: 10.1097/dad.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Among the Histological Features of Psoriasis

Abstract: Eosinophils are absent in psoriasis" has been dogma for generations; yet, there is little published to support this statement. Two recent studies examining the presence of eosinophils in psoriasis came to contrasting conclusions. We reviewed skin biopsies from 50 patients with clinically confirmed cases of psoriasis vulgaris to characterize the histologic features, with a focus on the number of eosinophils in the dermis. We noted the presence of eosinophils in nearly half of our study population (n = 23, 46.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…[9][10][11] Prior studies have observed dermal eosinophils present in 46% and 49% of their patients, respectively. 9,11 These studies used different methods to quantify the number of eosinophils present.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[9][10][11] Prior studies have observed dermal eosinophils present in 46% and 49% of their patients, respectively. 9,11 These studies used different methods to quantify the number of eosinophils present.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, total number of dermal eosinophils per tissue section was quantified in line with prior studies examining eosinophils in psoriasis. 9,10 Inflammatory cells present within vessels were excluded from all counts. All other categories were characterized by presence vs absence of each feature (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them were observed positively correlated with several T H 2‐related and T activation markers, a reasonable explanation for strong T H 2 component in cluster 1. It had been acknowledged that eosinophils were absent in psoriasis, 28 and however, recent studies revealed that eosinophils are not uncommon in the dermis of psoriasis and might accelerate psoriatic inflammation by supporting an inflammatory milieu that promotes neutrophil infiltration 29,30 . Therefore, the presence of eosinophils might be an indicator of neutrophil infiltration, rather than a T H 2‐skewed feature.…”
Section: Discussionmentioning
confidence: 99%
“…Vyas and coworkers conducted a detailed comparison of AGEP and pustular psoriasis [125]. They demonstrated a significant association between AGEP and the presence of eosinophils, although single necrotic keratinocytes as well as eosinophils were seen in both diseases, and sparse dermal eosinophils are a well-documented finding in psoriasis [126][127][128]. There was a tendency for AGEP to exhibit both subcorneal and deeper intraepidermal pustules, whereas pustular psoriasis showed mostly subcorneal pustules.…”
Section: Differential Diagnosismentioning
confidence: 99%